Gambaran Pemeriksaan Ultrasonografi pada Pasien Struma di Bagian/SMF Radiologi RSUP DR. M. Djamil Periode Januari–Desember 2019 - Irfan Fadilah; Dina Arfiani Rusjdi; Dinda Aprilia (Jurnal Ilmu Kesehatan Indonesia, 2021)
Background: A goiter is an enlargement of the thyroid gland caused by abnormalities of the thyroid gland in the form of malfunctioning or disorders of the structure of the gland and its morphology. According to WHO, the incidence of goiter is still quite high with iodine deficiency as the main cause. Objective: This study aims to determine the description of ultrasound examinations in goiter patients in Department of Radiology DR. M. Djamil January-December 2019 period. Method: This research was a retrospective descriptive study using cross sectional method using secondary data on 123 patients with thyroid goiter who meet the inclusion criteria in RSUP DR. M. Djamil Padang period January 2019-December 2019. The sampling method used a total sampling technique. Result: The results showed that 112 patients with thyroid goiter disorders met the inclusion criteria. The most clinical diagnosis results were goiter nodusa as many as 61 people (54.5%). The highest incidence was in the age range 41-50 years with 35 people (31.3%). The most gender was 88 women (78.6%). The results of ultrasonography in most goiter patients were diffuse in 43 people (38%).Conclusion: The conclusion of this study, it was found that the most age group of patients suffering from goitre were 41-50 years old, the majority of goiters occurred in the female compared to the male and the results of the most thyroid ultrasound images were diffuse goiter